Combinação de métodos de inoculação de Azospirillum brasiliense com adubação nitrogenada de cobertura aumenta produtividade de milho - Müller, Tânia Maria; Sandini, Itacir Eloi; Rodrigues, João Domingos [UNESP]; Novakowiski, Jaqueline Huzar; Basi, Simone; Kaminski, Tatyanna Hyczy (FapUNIFESP (SciELO), 2016)
Nitrogen (N) is the most limiting nutrient for corn production. Thereby, the goal of the paper was to evaluate inoculation methods of Azospirillum brasilense in order to partially supply N required by the crop. The experiment was carried out in Guarapuava, PR, Brasil, in 2011/2012 growing season. Randomized blocks with factorial 3 inoculation methods (seed treatment, planting furrow and non-inoculated control) x 5 doses of nitrogen (0, 75, 150, 225 and 300kg ha-1) x 8 replications was used as the experimental design. Leaf are index, foliar nitrogen content, total chlorophyll, grains per ear and yield were evaluated. There was significant interaction between inoculation methods and nitrogen fertilization to leaf area index, but not for yield. Inoculation with the diazotrophic bacteria provided yield increase of 702kg ha-1 for inoculation in seeding furrow and 432kg ha-1 for inoculation in seed treatment compared to the control, but both treatments did not differ between each other. Furthermore, total chlorophyll, grains per ear and yield were positively affected, with quadratic response, by the nitrogen fertilization in broadcasting.
Combination of inoculation methods of azospirilum brasilense with broadcasting of nitrogen fertilizer increases corn yield
Keywords: Diazotrophic bacteria; Nitrogen fertilization; Planting furrow; Seed treatment